2012
DOI: 10.1007/s12264-012-1287-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Aβ clearance and neurotrophic factors as a potential treatment for Alzheimer’s disease

Abstract: There is no effective drug to treat Alzheimer's disease (AD), a neurodegenerative disease affecting an estimated 30 million people around the world. Strongly supported by preclinical and clinical studies, amyloid-beta (Aβ) may be a target for developing drugs against AD. Meanwhile, the fact that localized neuronal death/loss and synaptic impairment occur in AD should also be considered. Neuronal regeneration, which does not occur normally in the mammalian central nervous system, can be promoted by neurotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…CPE is an emerging and a promising therapeutic target for neurodegenerative diseases. Encouragingly, clinical trials have shown that neurotrophic factors are potentially effective in treating AD [32] . Thus, continued investigations into the function of CPE/NF-α1 as a new trophic factor are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…CPE is an emerging and a promising therapeutic target for neurodegenerative diseases. Encouragingly, clinical trials have shown that neurotrophic factors are potentially effective in treating AD [32] . Thus, continued investigations into the function of CPE/NF-α1 as a new trophic factor are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide accumulates during the course of AD and has been linked to memory impairments and dysfunctional neurons in the cortex and hippocampus. 71 Particularly, Aβ-peptide appears to be formed in autophagosomes, which also appear to contain presenilin-1 enzymes and APP that help break down APP into Aβ-peptide. Autophagy conditions may also have a substantial impact on the -peptide release into extracellular space, which leads to the development of plaques.…”
Section: Therapeutic and Pharmacological Approaches To Activate Autop...mentioning
confidence: 99%
“…However, the Aβ peptide derived from the successive splitting of amyloid precursor protein (APP) through the β-site APP cleavage enzyme 1 (BACE1) and γ-secretase also has been linked to neurodegeneration. Accumulation of this peptide has been shown to cause cognitive deficits and neuronal dysfunction in the cortex and hippocampus during AD pathogenesis ( 40 ). Particularly, Aβ may also be produced in autophagosomes, which seem to comprise APP and presenilin-1 enzymes that participate in the cleavage of APP to Aβ ( 41 ).…”
Section: Clearence Of Aggregate-prone Proteins Through Autophagy In Nmentioning
confidence: 99%
“…Furthermore, statin, a class of lipid-lowering medications, has been demonstrated to induce autophagy in astrocyte cultures through AMPK-mTOR mediated pathways, and as it has been suggested that autophagy is essential in insulin-degrading enzyme secretion, modulation of autophagy could provide a possible therapeutic approach in Aβ pathology by increasing clearance of extracellular Aβ ( 98 ). Hence, accumulation of Aβ peptide participates in the pathological condition of AD, while inhibiting Aβ production or increasing Aβ removal may be implicated in slowing the progression of AD ( 40 ). In particular, the promotion of Aβ clearance is currently considered to be an additional therapeutic approach for AD.…”
Section: Therapeutic Implications Of Autophagy In Neurodegenerationmentioning
confidence: 99%